2020
DOI: 10.1080/15287394.2020.1728598
|View full text |Cite
|
Sign up to set email alerts
|

A suggested bisphenol A metabolite (MBP) interfered with reproductive organ development in the chicken embryo while a human-relevant mixture of phthalate monoesters had no such effects

Abstract: Mattsson (2020) A suggested bisphenol A metabolite (MBP) interfered with reproductive organ development in the chicken embryo while a human-relevant mixture of phthalate monoesters had no such effects,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 83 publications
(118 reference statements)
0
6
0
6
Order By: Relevance
“…A total of 160 fertilized Leghorn eggs were obtained from the University of Delaware research farm and used in the assay. The chicken embryo as an in vivo model using early life stages has been widely used in toxicity assessment (Mentor, Bornehag, et al, 2020; Uggini et al, 2012; Zhang et al, 2021). The eggs were weighed and divided into 17 groups: vehicle control; two dosages of guaiacol, syringol, and three S/G mixtures (at ratio 0.5, 1, and 2); and three plant lignin monomers (MC, pine, and poplar).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 160 fertilized Leghorn eggs were obtained from the University of Delaware research farm and used in the assay. The chicken embryo as an in vivo model using early life stages has been widely used in toxicity assessment (Mentor, Bornehag, et al, 2020; Uggini et al, 2012; Zhang et al, 2021). The eggs were weighed and divided into 17 groups: vehicle control; two dosages of guaiacol, syringol, and three S/G mixtures (at ratio 0.5, 1, and 2); and three plant lignin monomers (MC, pine, and poplar).…”
Section: Methodsmentioning
confidence: 99%
“…In all chicken embryos (male and female), the same chemical induced abnormal Mullerian duct retention and altered gonadal morphology. Development of feminization in male gonads suggested an estrogenic mode of action produced by MBP, whereas the decrease in ovary size in females suggested an antiestrogenic mode of action. It has also been reported that MBP had more potent estrogenic activity than parent BPA …”
Section: Common Endocrine-disrupting Chemicals (Edcs) and Evaluation ...mentioning
confidence: 99%
“…Sex-differentiation and reproductive organ development are similar in respect to cellular and molecular mechanisms between human and birds, which enable the chicken embryo to be a very useful tool for toxicity evaluation of EDCs. MBP­(4-Methyl-2,4-bis­(4-hydroxyphenyl) pent-1-ene), a major active BPA metabolite, upregulated female associated gonadal gene CYP19A1, FOXL2 and DMC1 expressed in male embryos and reduced expression of the testicular marker gene SOX9 . In all chicken embryos (male and female), the same chemical induced abnormal Mullerian duct retention and altered gonadal morphology.…”
Section: Common Endocrine-disrupting Chemicals (Edcs) and Evaluation ...mentioning
confidence: 99%
“…There is a long tradition of using avian embryos to study sexual development and potential effects of environmental pollutants including EDCs ( Berg et al, 1998 ; Berge et al, 2004 ; Biau et al, 2007 ; Eising et al, 2001 ; Estermann, Major & Smith, 2021 ; Fry & Toone, 1981 ; Ioannidis et al, 2021 ). It is well known that the exposure of xenobiotics during avian embryonic development can induce irreversible deformities or malformations of the sex organs and disrupt sex-specific behavior ( Farhat et al, 2020 ; Guioli et al, 2020 ; Harnett et al, 2021 ; Mentor et al, 2020a ; Mentor et al, 2020b ; Ottinger et al, 2008 ; Quinn, Summitt & Ottinger, 2008 ; Sharin et al, 2021 ). One advantage is that the avian egg can be considered as a closed system lacking any exchange with its environment except for the interchange of gases.…”
Section: Introductionmentioning
confidence: 99%